Stepping into the Future: Career Planning for Class XII Students Majoring in Hospitality at Vocational High Schools - Ramadhany, Army; Mengo, Nyabisi; Seif, Shiva (Journal of Social Knowledge Education (JSKE), 2022)
Purpose of the study: to describe the career planning of class XII students majoring in Hospitality at SMK Negeri 1 Merangin. Methodology: The research method used in this study is quantitative descriptive. The sample in this study was 30 students of XII Hospitality Department at SMK Negeri 1 Merangin. The data collection instrument used in this research was a questionnaire. Research data analysis will be carried out using descriptive statistical methods. Main Findings: The results from the descriptive statistics of career planning for twelfth-grade Hospitality students on the understanding of career choices indicator were obtained with an average in the good category at a percentage of 60%, on the readiness to enter the workforce indicator with an average in the good category at a percentage of 66.7%, and on the knowledge about career opportunities in the hospitality industry indicator with an average in the good category at a percentage of 60%. Novelty/Originality of this study: The novelty of this research lies in the special focus on career planning for class XII students majoring in Hospitality at SMK Negeri 1 Merangin. This research makes a significant contribution in broadening our understanding of how students at vocational education level, particularly in the hospitality sector, plan and prepare for their careers after graduating from school.